Diseño definitivo comparativo del puente de 60.0 m. de luz sobre el rio Toachi en base a las normas AASHTO estandar y LRFD - Prieto Salazar, Juan Carlos (2010)
The use of the new rules in the country will be a slow process to which you must go going, so it is necessary to be oriented to the new professionals to the knowledge of these new specifications so that they can apply as soon as possible. As you can understand, the specifications are extensive, so it is necessary to be adopted in parts, for which a field of application of the rules in order to familiarize them.